Mortalidade materna e a pandemia de COVID-19 no Brasil: uma análise das disparidades raciais e das mobilizações para seu enfrentamento - Palinski, Jane da Rosa (Universidade do Vale do Rio dos Sinos, 2022)
“Eight out of ten pregnant and postpartum women who died of coronavirus in the world were Brazilian” was a headline that circulated on digital networks in July 2020 and whose baseline study triggered a series of mobilizations and collective actions in Brazilian territory to diagnosis and confrontation the situation. This study aimed to analyze how these social mobilizations and actions for the prevention of maternal mortality were constructed in the context of the COVID-19 pandemic in Brazil and how the dimension of racism and other inequalities operating in the social production of these deaths. For decades, studies have shown that racial and class inequalities are dimensions that produce preventable maternal deaths in Brazil. This phenomenon was aggravated by the COVID-19 pandemic, as well as the political and economic situation in the country. A documentary research was carried out, with a corpus consisting of a variety of materials (lives, technical notes, audiências públicas, etc.) that circulated on the internet. Our spatial cut covers the national level, bringing some data from Rio Grande do Sul, as an action by the government, related to the National Day for the Reduction of Maternal Mortality, was highlighted; as well as São Paulo, with mobilization related to the vaccination of pregnant women in the state. A content analysis was carried out with two axes that articulated empirical data and theoretical discussions: how was the production of epidemiological data and the mapping of inequalities operating in these deaths; and what were the forms of mobilization and translation into actions/strategies, questioning in both cases how the racial dimension was incorporated. The main results highlight the need to politicize maternal mortality within the demands for guaranteeing women's human rights, especially the right to life, whether in the qualification of the production of epidemiological data and the social determinants of preventable maternal deaths, as well as in implementation of equity policies that promote social justice.
Keywords: Mortalidade materna; COVID 19; Mobilizações; Disparidades raciais; Prevenção; Maternal mortality; Mobilizations; Racial disparities; Prevention; ACCNPQ::Ciências Humanas::Sociologia